Analisis Wedding Expo Sebagai Media Promosi Dalam Menarik Calon Klien CV. Affection Group - Tri Sayekti Herlina; Khoirotunnisa, Fani (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2026)
This study examines the effectiveness of the Wedding Expo as a promotional medium for attracting potential clients of CV. Affection Group. Using a descriptive qualitative approach through interviews, observations, and documentation, the research identifies how wedding exhibition events support interest, trust, and client conversion. The findings show that experiential promotional activities—such as photobooths, food testing, decoration showcases, and interactive visuals—successfully increase visitor attention and engagement. Strong branding preparation before the event further enhances the company’s image and encourages on-site consultations. Field results indicate that one Wedding Expo can generate up to 700 new prospects, demonstrating the higher impact of event-based promotion compared to non-interactive digital methods. Overall, the Wedding Expo is considered an effective and competitive promotional strategy to strengthen brand visibility and client conversion for CV. Affection Group.